Respuesta :
Answer:
We will simply solve them and get correct answers that will match the answers provided.
1. [tex]2x^{2}y+(x^{2}y-2xy^{2} )[/tex]
= [tex]3x^{2} y-2xy^{2}[/tex]
2. [tex](5xy^{2}-x^{2} y)+3x^{2} y[/tex]
= [tex]5xy^{2} +2x^{2} y[/tex]
3. [tex]4x^{2} y+(x^{2} y+xy^{2} )[/tex]
= [tex]5x^{2} y+xy^{2}[/tex]
4. [tex]x^{2} y+(-2xy^{2}-4x^{2} y)[/tex]
= [tex]-3x^{2} y-2xy^{2}[/tex]
Answer:
[tex]1.~ 2x^2y + (x^2y - 2xy^2) = 3x^2y - 2xy^2\\2.~(5xy^2 - x^2y) + 3x^2y=5xy^2 + 2x^2y\\3.~4x^2y +(x^2y +xy^2)= 5xy^2+ 2x^2y\\3.~4x^2y + (x^2y + xy^2)=5x^2y +xy^2\\4.~x^2y + (-2xy^2 - 4x^2y)=-3x^2y - 2xy^2[/tex]
Step-by-step explanation:
We have to match the given monomials and binomials.
Monomials:
[tex]2x^2y + (x^2y - 2xy^2)\\(5xy^2 - x^2y) + 3x^2y\\4x^2y + (x^2y + xy^2)\\x^2y + (-2xy^2 - 4x^2y)[/tex]
The given binomials are:
[tex]5xy^2 + 2x^2y\\ -3x^2y - 2xy^2 \\3x^2y - 2xy^2\\ 5x^2y + xy^2[/tex]
Solving the monomials and matching can be done in the following manner:
[tex]1.~ 2x^2y + (x^2y - 2xy^2)\\= 2x^2y + x^2y - 2xy^2 = 3x^2y - 2xy^2\\2.~(5xy^2 - x^2y) + 3x^2y\\=5xy^2 + 3x^2y - x^2y = 5xy^2 + 2x^2y\\3.~4x^2y + (x^2y + xy^2)\\= 4x^2y + x^2y + xy^2 = 5x^2y +xy^2\\4.~x^2y + (-2xy^2 - 4x^2y)\\= x^2y - 4x^2y-2xy^2 = -3x^2y - 2xy^2[/tex]